Regulation of three beta-tubulin mRNAs during rat brain development. - Ginzburg, I (1985)
The nucleotide sequence of a complete rat brain beta-tubulin T beta 15 has been determined from three overlapping cDNA clones. The overall length of the T beta 15 sequence is 1589 bp and shows between 84.5% and 88.6% homology within the coding region as compared with chick and human beta-tubulin sequences. On the other hand, the 3'-non-coding region is highly divergent. Comparison of the derived amino acid sequences from different species demonstrates that the amino acid changes are not randomly distributed, but rather there are several conserved and two highly variable regions common to beta-tubulin polypeptides from various sources. The T beta 15 sequence encodes a dominant neuronal 1.8-kb beta-tubulin mRNA species. Two other minor beta-tubulin mRNA species of 2.6 and 2.9 kb are present in rat brain. By using two synthetic oligonucleotide probes complementary to the carboxyl-terminal divergent region and to the amino-terminal conserved region, we have shown that the three mRNAs are distinct species, which are developmentally regulated. The level of the 1.8-kb mRNA species increases till the age of 12 days thereafter its level decreases. The 2.9-kb mRNA is an early neuronal mRNA species, while the 2.6-kb mRNA is a late neuronal species which is detected at 30 days of rat brain development. The data illustrate that there is a differential expression of the beta-tubulin multigene family during rat brain development which may suggest different functions for the various beta-tubulin isotopes.